Ownership Structure, Incentives, and Asset Returns - Jung, Hae Won (Henny); Subramanian, Ajay; Zeng, Qi (Management Science, 2024)
We develop a dynamic equilibrium model to derive the endogenous relations among firms’ ownership structures, managerial incentives, and asset returns. Ownership concentration is positively related to managerial incentives (PPS) but is negatively related to its expected stock (dollar) return, and volatility. If initial block ownership is above (below) its steady-state level, block ownership and managerial PPS decrease (increase) over time to their steady-state levels, whereas the expected stock returns, return volatilities, and the price impacts of block trades increase (decrease). The convergence of these variables to their respective steady-state levels is faster for firms that are less productive, that are riskier, and whose earnings are more sensitive to managerial actions. The price impact of block trades is larger in firms that are more productive and smaller in firms whose earnings are more sensitive to managerial actions. Changes in the expected stock return over time are negatively affected by changes in block ownership but positively affected by changes in managerial incentives. Relative to owner-managed firms, more widely owned firms have lower expected stock returns and volatilities, faster dispersion of block ownership, and smaller but more variable price impacts of block trades. Compared with diffusely owned firms, firms with significant blockholdings have lower expected stock returns, higher return volatilities, and less powerful managerial incentives. This paper was accepted by Tomasz Piskorski, finance. Funding: H. W. (H.) Jung and Q. Zeng received an internal research grant (AUD 15,000) in 2015 from the Faculty of Business and Economics at the University of Melbourne. Supplemental Material: The data files and online appendices are available at https://doi.org/10.1287/mnsc.2023.4696 .